The Correlation Between CO2 Emissions and GDP in a Sustainable Development Framework Using Kuznets Environment Curve - Cosma, Ioana Gabriela; David, Katalin Gabriela; Antonescu, Daniela; Dumiter, Florin Cornel; Jimon, Ștefania Amalia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
After 1990, the problem of finding econometric models to assess the influence of economic development on the environment becomes a global goal, a central element of regional, national and Community policies. A perception on the evolution of global climate change and on the impact of human activity on them has been determined by the hypothesis that in the early stages of economic development, pollution and incomes are growing almost simultaneously, and beyond a certain level of incomes, the trend is reversing, therefore at high levels of incomes and economic growth occur improvements in environmental conditions. In this paper, we aim to analyze the relationship between the level of pollution (CO2 emissions) and revenues (GDP per capita) using the Kuznets Environmental Curve (EKC). To apply the econometric model, two indicators were used: CO2 emissions and GDP per capita, using a panel analysis for the period 2000 - 2016, which included 31 European countries and 527 observations. The article contributes to the development of econometric applications based on panel data and the Kuznets Environmental Curve.